Fracture toughness of three heat pressed ceramic systems - Livia Fiorin; Guilherme Teixeira Theodoro; Izabela Cristina Maurício Moris; Renata Cristina Silveira Rodrigues; Ricardo Faria Ribeiro; Adriana Cláudia Lapria Faria (Universidade Estadual de Campinas, 2018)
Aim: The aim of this study was to evaluate fracture toughness by indentation method of three dental ceramics processed by heat pressing. The ceramics evaluated were fluorapatite glass ceramic (ZIR), glass ceramic containing leucite (POM) and leucite-reinforced glass ceramic (EMP). Materials and methods: Ninety disks (13mm of diameter x 4mm of thickness) and nine rectangular specimens (25x4x2mm) were made to evaluate, respectively, microhardness/fracture toughness (n=30) and elastic modulus (n=3). Samples were obtained by pressing ceramic into refractory molds. After polishing, Vickers microhardness was evaluated under 4,904N load for 20s. Elastic modulus was measured by impulse excitation technique. Data from microhardness and elastic modulus were used to calculate fracture toughness, after measuring crack length under 19,6N load applied for 20s. Results were evaluated by ANOVA and Tukey´s test. Results: Microhardness (VHN) of POM (637.9±53.6) was statistically greater (p<0.05) than ZIR (593.0±14.3), followed by EMP (519.1±21.5); no significant difference (p=0.206) was noted for elastic modulus (GPa) (ZIR: 71.5±9.0; POM: 67.3±4.4; EMP: 61.7±2.3). Fracture toughness (MPa/m) of POM (0.873±0.066) was statistically lower (p<0.05) than ZIR (0.977±0.021) and EMP (0.965±0.035). Conclusion: The results suggest that fluorapatite glass ceramic (ZIR) and leucite-reinforced glass ceramic (EMP) processed by heat pressing presented greater fracture toughness, improving clinical prognosis of metal free restorations.